2014
DOI: 10.3892/ijo.2014.2774
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma proteostasis can be targeted via translation initiation factor eIF4E

Abstract: Intensive protein synthesis is a unique and differential trait of the multiple myeloma (MM) cells. Previously we showed that tetraspanin overexpression in MM cell lines attenuated mTOR and PI3K cascades, induced protein synthesis, activated unfolded protein response (UPR), and caused autophagic death, all suggesting breach of proteostasis. Here we assessed the role of translation initiation in the tetraspanin‑induced MM cell death with emphasis on eIF4E translation initiation factor. We showed tetraspanins att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 45 publications
(40 reference statements)
3
28
1
Order By: Relevance
“…On the other hand, lack of EIF4E3 expression in relapsed samples was able to distinguish a second group of MM patient samples exhibiting the opposite phenotype and pathway activation states in which enhanced eIF4E1-driven translation was indicated. These findings are consistent with the results of other studies demonstrating a role of eIF4E1 in MM biology and proteasome inhibitor resistance [65, 9698]. It is particularly noteworthy therefore — especially in view of the documented oncogenic activity of EIF4E1 [75] — that WHSC1 -expressing MM patients with high EIF4E3 expression had less favorable outcomes than those with high EIF4E1 expression (Figure 12).…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, lack of EIF4E3 expression in relapsed samples was able to distinguish a second group of MM patient samples exhibiting the opposite phenotype and pathway activation states in which enhanced eIF4E1-driven translation was indicated. These findings are consistent with the results of other studies demonstrating a role of eIF4E1 in MM biology and proteasome inhibitor resistance [65, 9698]. It is particularly noteworthy therefore — especially in view of the documented oncogenic activity of EIF4E1 [75] — that WHSC1 -expressing MM patients with high EIF4E3 expression had less favorable outcomes than those with high EIF4E1 expression (Figure 12).…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies we have shown that eIF4E and eIF4GI are over-expressed in MM as well, and responsive to external soluble signals [17,18]. Furthermore, we showed that eIF4E and eIF4GI are necessary for maintaining MM cells' survival and proliferation as well as the expression of major signals integral to the malignant phenotype [18,19].…”
Section: Introductionmentioning
confidence: 73%
“…Taken together, these data suggest that high expression or at least a critical threshold of eIF4E is required for protein translation of transcription factors c-MYC, IRF4, and C/EBPb and therefore for malignant growth of multiple myeloma cells. The use of inhibitors that directly target the translation initiation complex eIF4F shows a promise effects in multiple myeloma (13)(14)(15)(16). Further, eIF4E also exhibits oncogenic potential that arises from its critical roles in the nuclear export and cytosolic translation of oncogenic transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…In multiple myeloma, ribavirin (RBV) is a physical mimic of the m 7 G cap, and thus blocks eIF4E resulting in a potentially effective anticancer agent. Combination of RBV and velcade showed synergistic anti-multiple myeloma effect (13). 4EGI-1 behaves as a functional 4E-BP1 mimetic inhibiting the interaction between eIF4E and eIF4G and decreases the expression of eIF4E-regulated proteins in myeloma cells (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation